Hazard Identification and OHS Risk Assessment at Animal Feed Company - Jordan Syah Gustav; Rizqy Kartika Sari; Ayu Prima Kartika; Nabylla Sharfina Sekar Nurriwanti; Warda Yussy Rha (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to identify hazards and assess occupational health and safety (OHS) risks in the animal feed production process using the HIRARC (Hazard Identification, Risk Assessment, and Risk Control) method. The feed industry involves various operational stages that pose significant safety risks to workers, particularly due to exposure to dust, noise, chemicals, and physically demanding tasks. A descriptive qualitative approach was employed, utilizing field observations and direct interviews with workers across different departments involved in the production line. The findings reveal a wide range of potential hazards at each stage of the feed manufacturing process. These include respiratory risks caused by airborne particles in confined spaces, noise exposure from machinery, musculoskeletal injuries due to repetitive and manual handling of heavy materials, and exposure to hazardous substances such as cleaning agents and chemical additives. Each identified hazard was assessed based on its likelihood of occurrence and severity of impact, resulting in a risk rating that was then used to prioritize necessary control measures. Risk mitigation strategies were proposed according to the hierarchy of controls, starting with elimination and substitution, followed by engineering controls such as improving ventilation and using noise-reducing equipment. Administrative controls like work rotation schedules, safety training, and the development of standard operating procedures were also emphasized. The use of personal protective equipment (PPE) is recommended as a supplementary measure rather than a primary control. By systematically applying the HIRARC method, this study provides a comprehensive overview of occupational risks in the animal feed industry. The recommended interventions are expected to contribute to a safer working environment, reduce accident rates, and improve the overall well-being and productivity of workers in feed production facilities.